O papel da molécula adaptadora fator de diferenciação mielóide 88 (MyD88) e dos receptores do tipo Toll (TLRs) na resposta imune contra a bactéria intracelular Brucella abortus - Gilson Costa Macedo (2007)
Brucella abortus is an intracellular pathogen, that undulant fever in humans and infertility among animals, resulting in serious economic losses. The initial host defense against bacterial infection is executed by innate immunity stimulated by pathogen-associated molecular patterns (PAMPs). These patterns are conserved molecular structures common to different groups of pathogens that are recognized by toll-like receptors (TLR). Myeloid differentiation protein (MyD88) is an adaptor molecule critical for TLR signaling. Activation of MyD88-dependent pathways results in signaling and induction of pro-inflammatory cytokines. It is not clear how innate immunity initially recognize and respond to Brucella and the data reported in the literature are still contradictory. The main goal of this study was to evaluated the role of MyD88 adaptor molecule and TLR2, TLR4 and TLR9 receptors in Brucella immune response in vivo.To determine the contribution of MyD88 in bacterial clearance, numbers of Brucella were monitored in the spleens of MyD88 KO and C57BL/6 mice at 1, 2, 3 and 6 weeks following B. abortus infection. The cytokines production was evaluated in lymph nodes cells (IFN-g and TNF-a) and macrophages (TNF-a and IL-12) stimulated by heat killer B. abortus (HKBa) S2308 or RB51 strains and their purified LPS and lipid A. Murine brucellosis was marked exacerbated in MyD88 KO at all intervals studied and the levels of IFN-g, TNF-a and IL-12 into the supernatant of HKBa, LPS or lipid A stimulated MyD88 KO cells were totally abrogated compared to wild-type mouse cells. This results show that MyD88 is critical for host resistance to Brucella abortus.Additionally, administration of recombinant cytokines in MyD88-/- mice demonstrated that only IL-12 increased the Brucella control by reducing bacterial load.In order to determine the role of TLRs in Brucella infection in vivo, TLR2, TLR4 and TLR9 KO mice were infected with virulent strain S2308 and quantified the number of bacteria in spleen. The results show that TLR2 and TLR4 are not required for clearance of Brucella in vivo. However, TLR9 deficiency enhances susceptibility to B. abortus infection probably due the fewer levels of IL-12 production. Indeed, our date show that CCL3 and CCL5 are partially dependent of TLR9 receptor and suggests a role for these chemokines in Brucella immune response.Thus, the present work confirms the predominant role of MyD88 in host resistant to B. abortus and it show that TLR9 receptor is important to mount an effective immune response against this pathogen. Finally, we demonstrated that the mechanism involved in MyD88-/- mice susceptibility relies an reduced IL-12 production by macrophages and dendritic cells.